2017
DOI: 10.1038/nature22072
|View full text |Cite
|
Sign up to set email alerts
|

The effect of illumination on the formation of metal halide perovskite films

Abstract: Optimizing the morphology of metal halide perovskite films is an important way to improve the performance of solar cells when these materials are used as light harvesters, because film homogeneity is correlated with photovoltaic performance. Many device architectures and processing techniques have been explored with the aim of achieving high-performance devices, including single-step deposition, sequential deposition and anti-solvent methods. Earlier studies have looked at the influence of reaction conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
215
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(237 citation statements)
references
References 30 publications
14
215
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] The power conversion efficiency (PCE) of perovskite solar cells (PSCs) has rocketed from 9% to 22.1% within the last 5 years, shocking the photovoltaic community. [1][2][3][4][5][6][7][8][9] The power conversion efficiency (PCE) of perovskite solar cells (PSCs) has rocketed from 9% to 22.1% within the last 5 years, shocking the photovoltaic community.…”
Section: Perovskite Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9] The power conversion efficiency (PCE) of perovskite solar cells (PSCs) has rocketed from 9% to 22.1% within the last 5 years, shocking the photovoltaic community. [1][2][3][4][5][6][7][8][9] The power conversion efficiency (PCE) of perovskite solar cells (PSCs) has rocketed from 9% to 22.1% within the last 5 years, shocking the photovoltaic community.…”
Section: Perovskite Solar Cellsmentioning
confidence: 99%
“…[22][23][24] These impacts on perovskite films could profoundly affect the performance of the final devices. [1][2][3][4][5][6][7][8][9] The power conversion efficiency (PCE) of perovskite solar cells (PSCs) has rocketed from 9% to 22.1% within the last 5 years, shocking the photovoltaic community. It is thus of vital importance to understand the interaction mechanism between different SVAs and perovskite films during/post the film-annealing process.…”
mentioning
confidence: 99%
“…1416 Many studies have focused on improving the deposition techniques and the crystal quality of perovskite films, and it was, for example, shown that illumination during film formation can enhance the quality of perovskite films. 17 …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The propensity of perovskite films for low-cost solution processing also encourages scientists to explore potential applications beyond solar cells. [1][2][3][4][5] The propensity of perovskite films for low-cost solution processing also encourages scientists to explore potential applications beyond solar cells.…”
mentioning
confidence: 99%